Gauging support for macroecological patterns in helminth parasites. Issue 12 (11th October 2018) - Dallas, Tad A.; Aguirre, A. Alonso; Budischak, Sarah; Carlson, Colin; Ezenwa, Vanessa; Han, Barbara; Huang, Shan; Stephens, Patrick R.
Abstract: Aim: To explore spatial patterns of helminth parasite diversity, and to investigate three main macroecological patterns – (a) latitude–diversity relationships, (b) positive scaling between parasite and host diversity, and (c) species–area relationships – using a largely underutilized global database of helminth parasite occurrence records. Location: Global. Methods: We examined the London Natural History Museum's collection of helminth parasite occurrence records, consisting of over 18, 000 unique host species and 27, 000 unique helminth parasite species distributed across over 350 distinct terrestrial and aquatic localities. Results: We find support for latitudinal gradients in parasite diversity and a strong relationship between host and parasite diversity at the global scale. Helminth species diversity–area relationships were not detectable as a function of host body mass, but larger geographic areas supported higher parasite richness, potentially mediated through higher host richness. Main conclusions: Our findings indicate that helminth parasites may obey some of the macroecological relationships found in free‐living species, suggesting that parasites may offer further support for the generality of these patterns, while offering interesting counterexamples for others. We conclude with a discussion of future directions and potential challenges in the newly emerging macroecology of infectious disease.